Rekonstruksi Ekowisata dan Pemberdayaan Ekonomi Masyarakat melalui Halal Tourism - Sofiah, Sofiah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
Islamic economics is the center of world attention with all interesting aspects, including sharia economics. Indonesia is a country with enormous potential in the development of an Islamic economy, especially in the halal tourism sector. Indonesia has qualified provisions to develop halal tourism from natural resources and human resources. Indonesia has very beautiful places and the largest Muslim majority in the world. This study aims to describe the reconstruction of ecotourism development through halal tourism and to determine the impact of applying the concept of halal tourism related to the potential of ecotourism for economic empowerment in Indonesia. The method used is descriptive qualitative which is literary research. The results show that halal tourism in Indonesia is one of the pillars of the Indonesian economy through its contribution to the country's foreign exchange. On the other hand, halal tourism will be able to be a conclusion of previous tourism problems, especially the destruction of nature due to excessive exploitation by humans themselves.